Penjadwalan Dinas Pegawai Menggunakan Algoritma Genetika Pada PT Kereta Api Indonesia (KAI) Daerah Operasi 7 Stasiun Besar Kediri - Yolanda Nailil Ula; Dian Eka Ratnawati; Satrio Agung Wicaksono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Scheduling is one thing that very important to create regularity organizational activities in the company, especially about the scheduling employee service. In this study data schedule employee PT Kereta Api Indonesia Kediri Besar Station in 2017, for optimal scheduling result use genetic algorithm method base on company regulation. In the genetic algorithm process initial population process is done by chromosome representation using permutation number with length of gene 98 representing 14 employees in 7 days. The reproduction process is divided into crossover and mutation, the crossover method use one cut point, and the mutation method use reciprocal exchange mutation. The selection process is done by elitism selection with selecting the fitness value based on the best result to be the parents in the next generation. Based on the test results are obtained the optimal parameters of cr value 0,1 mr value 0,9 in the 50 th generation and population 50 with average fitness value 0,093.